ANALYSIS OF EFFECTIVENESS OF ECONOMICS SUBJECT TUTORING AFTER SCHOOL - Sabar Narimo; Septi Anggraini; Suranto Suranto; Dhany Efita Sari; Ramlee Musthapa (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2022)
Tutoring is an additional learning activity after school to improve students’ learning outcomes. Tutoring can be conducted by informal or institution, in small groups, or large groups. This study aims to describe the factors influencing students of tutoring after school and the strategy of after-school tutoring program company for school exams and to test students’ outcomes after following after-school tutoring. The participants were 30 students of third grade of senior high school majoring in social sciences. Data collection was conducted using questionnaires, documentation, and observation. The data analysis technique is paired sample t-test. The independent variable is students before taking tutoring and students after following tutoring as the dependent variable. Based on paired sample t-test. It was found that t-count t-table is -2.066 -1.699. The results show a positive influence and significantly showed that tutoring succeeded in improving students’ learning outcomes.